THE INFLUENCE OF EDUCATIONAL LEVEL AND ACCOUNTING KNOWLEDGE ON THE IMPLEMENTATION OF DIGITALIZATION OF ACCOUNTING INFORMATION - Maya Dini; Ria Astri Yani; Rusma Rizal; Agustina Prativi Nugraheni (Jurnal Manajemen, 2024)
Research to determine the influence of educational level and accounting knowledge on the implementation of digitalization of accounting information (for food and beverage micro businesses in Palembang City). Using primary data in the form of a questionnaire to 270 respondents withusing the lameshow formula to determine the number of samples whose population is above 1,000 people. The research results show that educational level and accounting knowledge influence the implementation of digitalization of accounting information.